2018
DOI: 10.1111/jmi.12700
|View full text |Cite
|
Sign up to set email alerts
|

Automated detection of fluorescent cells in in‐resin fluorescence sections for integrated light and electron microscopy

Abstract: SummaryIntegrated array tomography combines fluorescence and electron imaging of ultrathin sections in one microscope, and enables accurate high‐resolution correlation of fluorescent proteins to cell organelles and membranes. Large numbers of serial sections can be imaged sequentially to produce aligned volumes from both imaging modalities, thus producing enormous amounts of data that must be handled and processed using novel techniques. Here, we present a scheme for automated detection of fluorescent cells wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 26 publications
2
14
0
Order By: Relevance
“…With respect to the cell segmentation, the results show a rather low inter-observer agreement with an F-score of 0.39 for cell segmentation in DAPI-stained images and 0.45 for cell segmentation in PHH3-stained images. This low agreement has also been reported for other fluorescence microscopy datasets, and is likely related to the smaller surface area to volume ratio of cell structures compared to tissues [30] as well as blurry cell edges even where the focus is optimal. In order to assess the extent to which the quality of the scans affects the human and automatic segmentation, the image focus assessment method proposed by Yang et al [11] was used.…”
Section: Cell Segmentationsupporting
confidence: 47%
“…With respect to the cell segmentation, the results show a rather low inter-observer agreement with an F-score of 0.39 for cell segmentation in DAPI-stained images and 0.45 for cell segmentation in PHH3-stained images. This low agreement has also been reported for other fluorescence microscopy datasets, and is likely related to the smaller surface area to volume ratio of cell structures compared to tissues [30] as well as blurry cell edges even where the focus is optimal. In order to assess the extent to which the quality of the scans affects the human and automatic segmentation, the image focus assessment method proposed by Yang et al [11] was used.…”
Section: Cell Segmentationsupporting
confidence: 47%
“…Integrated CLEM instruments (with the LM built in the EM) greatly facilitate retracing of the ROI from FM to EM (Koning et al, 2019; Liv et al, 2013), since the coordinate systems of the FM-EM are shared. Recently, multiple integrated (confocal) FM and volume-EM systems were reported (Ando et al, 2018; Brama et al, 2016; Delpiano et al, 2018; Gorelick et al, 2019; Lane et al, 2019). We add to this a home-built system integrating a Confocal Laser Scanning Microscope (CLSM) into a Focused Ion Beam / Scanning Electron Microscope (FIB.SEM), similar in geometry to a previously reported (Timmermans et al, 2016) integrated system and as outlined in Supplementary Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…We and others have shown that linking functional or dynamic information obtained with live-cell imaging to the underlying fine structure of the cell opens up powerful possibilities to study mechanistic processes with respect to their ultrastructure (Collinson et al, 2017; Fermie et al, 2018; Russell et al, 2016). Correlation with live-cell FM also aids the identification and capture of rare cellular structures or events, which is very challenging, time demanding, and at times basically impossible without smart tracking for EM imaging (Burel et al, 2018; Delpiano et al, 2018). An integrated CLEM platform provides exactly these requirements by enabling a direct translation between live-cell FM and volume-EM and the targeting identified live-cell events for follow-up ultrastructural imaging.…”
Section: Introductionmentioning
confidence: 99%
“…Regions of interest (ROI) were selected between imaging rounds for successive, targeted acquisitions down to 4 nm/px resolution, thereby reducing the time it would otherwise take to fully image the full brain at high resolution. Similarly, Delpiano et al (2018) used detection of in-resin preserved fluorescence in an integrated light and electron microscope for automated guiding to ROIs for subsequent acquisition. Other approaches involve parallelizing the imaging load across multiple instruments.…”
Section: Introductionmentioning
confidence: 99%